The effect of object texture, ground texture and motion vector tilt on perception of accelerated approach of the object - Luka Komidar (Psihološka Obzorja, 2004)
Human observers do not accurately perceive acceleration of neither motion in frontal plane nor motion in depth. Recent studies simulated motion in depth by changing only relative size of the object. The purpose of this study was to investigate the influence of various levels of representation of depth on perception of accelerated motion (object approach) in depth. Additionally to using the changing size cue, we used three sources of depth information: object texture, ground texture, and motion vector tilt. We discovered that the chosen sources of information had significant effects on the perception of accelerated motion in depth. When only looming was present in the viewing scene, observers perceived decelerated motion in depth as constant. The result could be interpreted in terms of the foreshortening of perceived depth. The main effects of the three sources of depth information were similar: they did not improve sensitivity for motion acceleration, but with their presence motion had to be more accelerated (less decelerated) to be perceived as linear. Object texture was the least influential source of information, whereas motion vector tilt was the most influential. When motion vector was tilted for 15°, approach had to be accelerated in order to be perceived as linear. We argue that the latter effect was due to the frontal-plane motion vector when height in visual field was present, which in turn relates to the findings that motion in frontal plane has to be accelerated in order to be perceived as constant. We also found that object texture consistently decreased the effects of ground texture and motion vector tilt. The obtained interactions among the three sources of information indicate that these sources integrate as proposed by the modified weak fusion model.